Integrasi Pendidikan Akidah Akhlak dalam Kurikulum Sekolah dan Perguruan Tinggi - Willy Akmansyah Lubis (An-Nuha, 2023)
Akidah akhlak education is a fundamental element in shaping the character and personality of students based on the values of Islamic faith and morality. In the context of increasingly complex globalization and value crises, the integration of faith and moral values in the formal education system is an urgent need so that the education process not only produces intellectually intelligent people, but also spiritually and ethically superior. This study aims to examine the concept, practice, model, and evaluation of the integration of faith and moral education in the school and college curriculum. The main focus of the study covers five aspects, namely: the concept of integration in national education, integration practices in elementary and secondary schools, integration in Islamic college environments, learning models and approaches, and evaluation of the success of the integration of faith and moral values. The method used is library research with documentation techniques on various scientific sources such as books, journals, educational regulations, and previous research results. The results of the study indicate that the integration of faith and moral education is very relevant and necessary at every level of education. In schools, integration is carried out through thematic learning and value habituation, while in universities using an andragogical approach that emphasizes discussion, reflection, and case studies based on Islamic values. The Webbed Model and pedagogical-andragogical approach have proven effective in supporting the integration of spiritual values in learning. Evaluation of the success of integration involves cognitive, affective, and psychomotor aspects through observation, questionnaires, portfolios, and self-assessment. Overall, these findings emphasize the importance of contextual and collaborative strategies to ensure the internalization of faith and moral values in the education system as a whole and sustainably.